(3ebGdI aj cTa YhQGJ GdHGWfjI HeG ehghG Ydi YGeJge aj QDjI GdCgdjIs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3bO PcQfG ai GdeLSWi GdTGgi GdPi YdefGg cjajI ETJQGc GdCehQ GdWHjYjI eY Yde GdgjFI ai QDjI GdCgdI hfQjO GdEfSGf s
(3BNQgG (B:s
(3hJQSN ai bdHg Gdeehg ef GdRhQ QShNkG dG jRhd jO GdeSfO afSCd Gddg GdJhajb hGdYUeI Hefg JeJ GdebGdI hGdMeO ddg QH GdYGdejf hUdhGJg Ydi fHjg eMeO hBdg GdWGgQjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds